Total anomalous pulmonary venous connection in 80 patients: Primary sutureless repair and outcomes - Li, Gefei; Meng, Baoying; Zhang, Cheng; Zhang, Weimin; Zhou, Xiaodong; Zhang, Qing; Ding, Yiqun (Frontiers in Surgery, 2023)
The Purpose of this research is to summarize the outcomes and relevant risk factors of 80 total anomalous pulmonary venous connection (TAPVC) patients who underwent primary TAPVC sutureless repair and discuss the indications and benefits of primary sutureless repair. This retrospective review included 80 patients with TAPVC who underwent primary sutureless repair at a single institution between January 2015 and December 2020. Patients were subdivided into 4 groups according to Darling's classification. Risk factors that increase the postoperative pulmonary vein flow velocity were explored by Multiple Linear regression. Anatomic TAPVC subtypes included supracardiac 35 (43.8%), cardiac 24 (30%), infracardiac 17 (21.2%), and mixed 4 (5%). Median age at repair was 16.5 days and median weight was 3.5 kg. Preoperative pulmonary venous obstruction (PVO)was presented in 20 (25%) patients. There were 2 early deaths and 1 late death. 2 patients developed postoperative PVO and none required reintervention. Prolonged cardiopulmonary bypass time(CPB) (p=0.009), preoperative pneumonia (p= 0.022) and gender(p=0.041)were found to be associated with the increase of postoperative pulmonary vein flow velocity. Under the primary sutureless technique, no statistical difference was observed among the 4 subgroups in terms of postoperative pulmonary vein flow velocity (p=0.589). The primary sutureless technique may eliminate the differences between subtypes while decrease the postoperative PVO rate, which makes it applicable in any subtypes of TAPVC. Following the favorable outcomes in preventing postoperative PVO in all subtypes in this study, we advocate the indications for primary sutureless repair may expand further to all the TAPVC patients.